2021
DOI: 10.2196/26344
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for the Design and Implementation of Virtual Reality for Acquired Brain Injury Rehabilitation: Systematic Review

Abstract: Background Virtual reality (VR) is increasingly being used for the assessment and treatment of impairments arising from acquired brain injuries (ABIs) due to perceived benefits over traditional methods. However, no tailored options exist for the design and implementation of VR for ABI rehabilitation and, more specifically, traumatic brain injury (TBI) rehabilitation. In addition, the evidence base lacks systematic reviews of immersive VR use for TBI rehabilitation. Recommendations for this populati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 114 publications
5
50
0
Order By: Relevance
“…Dietrich et al ( 2021 ) describe two case studies on VR applications for alcohol abuse prevention, and compare different co-design methodologies. Brassel et al ( 2021 ) provide a review of design principles for VR applications in the field of brain injury rehabilitation, and conclude that co-design is an important component.…”
Section: Discussionmentioning
confidence: 99%
“…Dietrich et al ( 2021 ) describe two case studies on VR applications for alcohol abuse prevention, and compare different co-design methodologies. Brassel et al ( 2021 ) provide a review of design principles for VR applications in the field of brain injury rehabilitation, and conclude that co-design is an important component.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, three systematic reviews assessed the effects of physical rehabilitation on cognition, and one demonstrated positive effects in the general adult population (Fritz, Cheek, and Nichols-Larsen, 2015). Of the other two systematic reviews, one exclusively examined populations of veterans (Wilson et al, 2016), and one drew uncertain conclusions (Brassel et al, 2021). Four systematic reviews assessed the effects of occupational rehabilitation interventions on cognition.…”
Section: Cognitivementioning
confidence: 99%
“…Fourteen of those reviews demonstrated effectiveness (Bogdanova et al, 2016;Cicerone et al, 2005;Cicerone et al, 2011;Elliott and Parente, 2014;Fritz, Cheek, and Nichols-Larsen, 2015;Hallock et al, 2016;Kennedy et al, 2008;Lambez and Vakil, 2021;Little, Byrne, and Coetzer, 2021;O'Neil-Pirozzi, Kennedy, and Sohlberg, 2016;Park, Maitra, and Martinez, 2015;Radomski et al, 2016;Rodríguez-Rajo et al, 2018;Rohling et al, 2009), and two demonstrated no effect Virk et al, 2015). Additionally, three reviews had mixed findings (Cicerone et al, 2019;Roitsch et al, 2019;Steel, Elbourn, and Togher, 2021), and four characterized the evidence as uncertain (Ali, Viczko, and Smart, 2020;Brassel et al, 2021;Geraldo et al, 2018;Schrijnemaekers et al, 2014). Two systematic reviews assessed the effect of behavioral rehabilitation on cognitive outcomes, demonstrating effectiveness in the general adult population (Little, Byrne, and Coetzer, 2021) and uncertain conclusions in populations restricted to veterans (Wilson et al, 2016).…”
Section: Cognitivementioning
confidence: 99%
See 1 more Smart Citation
“…This would enable a more personalized “prescription” of VR interventions to patients for whom it would be most useful. More recent research has noted the importance of considering patient characteristics such as motor, visual, or vestibular impairments in the design and implementation of VR for patients with acquired brain injuries, as lack of such consideration could be a barrier to the use of VR by this group [ 33 ].…”
Section: Introductionmentioning
confidence: 99%